2006
DOI: 10.1159/000104861
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Psychological Stress in Inflammatory Bowel Disease

Abstract: Inflammatory bowel disease (IBD) is an idiopathic inflammatory condition of the gastrointestinal tract whose natural history is one of periods of remission and relapse. The aetiology is complex and reflects an interaction between genes and environment. Psychological stress has long been reported by both doctors and patients as worsening disease activity in IBD. Prospective studies of the relationship between disease relapse and adverse life events have produced conflicting results, in part due to the inherent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
54
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(65 citation statements)
references
References 125 publications
9
54
0
2
Order By: Relevance
“…Models of disease course as well as disease-specific quality of life were different in the two diseases, suggesting that UC and CD should be treated separately and not as one common IBD group in psychotherapeutic intervention studies. Previous studies evaluating the relationship of stress to relapse in IBD reported mixed results, 6,41,42 but prospective studies have linked UC more strongly than CD to perceived stress 21,23 ; our results indirectly support this. Moreover, our findings are in agreement with results from the largest psychotherapeutic intervention study in CD patients, 10 and from studies of psychological intervention studies in studies of mixed samples of IBD 11,12 or IBD patients with psychiatric problems such as high anxiety.…”
Section: Discussionsupporting
confidence: 76%
“…Models of disease course as well as disease-specific quality of life were different in the two diseases, suggesting that UC and CD should be treated separately and not as one common IBD group in psychotherapeutic intervention studies. Previous studies evaluating the relationship of stress to relapse in IBD reported mixed results, 6,41,42 but prospective studies have linked UC more strongly than CD to perceived stress 21,23 ; our results indirectly support this. Moreover, our findings are in agreement with results from the largest psychotherapeutic intervention study in CD patients, 10 and from studies of psychological intervention studies in studies of mixed samples of IBD 11,12 or IBD patients with psychiatric problems such as high anxiety.…”
Section: Discussionsupporting
confidence: 76%
“…In terms of the association between variables experienced in one 3-mo period and a symptomatic flare in the next 3-mo period, only psychological factors, including the occurrence of a major life event, high perceived stress, and high negative mood during a previous 3-mo period, were significantly associated with the subsequent occurrence of a flare. This study complements the growing evidence from experimental as well as clinical studies that stress exposure, including stressful events and perceived stress (the individual's view of his or her own level of demand relative to resources), may contribute to relapse risk in IBD [14][15][16][17][18] . In fact, using multivariate logistic regression analyses of these variables, only high perceived stress (adjusted OR = 2.40; 95%CI: 1.35-4.26) was associated with an increased risk of flare.…”
Section: Psychological Symptoms In Ibdsupporting
confidence: 59%
“…Il apparaît que les patients atteints de la MC utilisent davantage de straté gies é motionnelles de coping comme, par exemple, des straté gies centré es sur l'é vitement ou la fuite [11]. Ainsi, l'utilisation privilé gié e de straté gies de coping centré es sur l'é motion paraît augmenter la vulné rabilité des patients à rechuter [23,24] alors que la mise en place par le patient d'autres straté gies de coping n'engendrant pas de dé tresse psychologique ré duirait ce risque de ré cidive [17,18]. La dé tresse é motionnelle comme facteur de rechute fait l'objet de nombreux travaux, au dé triment de la qualité de vie.…”
Section: Introductionunclassified